2017
DOI: 10.1136/bmjopen-2016-014680
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional observational assessment of quality of newborn care immediately after birth in health facilities across six sub-Saharan African countries

Abstract: ObjectiveTo present information on the quality of newborn care services and health facility readiness to provide newborn care in 6 African countries, and to advocate for the improvement of providers' essential newborn care knowledge and skills.DesignCross-sectional observational health facility assessment.SettingEthiopia, Kenya, Madagascar, Mozambique, Rwanda and Tanzania.ParticipantsHealth workers in 643 facilities. 1016 health workers were interviewed, and 2377 babies were observed in the facilities surveyed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
84
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(94 citation statements)
references
References 29 publications
(29 reference statements)
10
84
0
Order By: Relevance
“…In our study 27 (11%) Neonates were died due to birth asphyxia after resuscitation which is similar with study done in six sub-Saharan Africa [59] but lower than study done in Tigray 31% [60] and in Jimma 23.2% [61] of Ethiopia and in Tanzania dar es salaam 62.5% [33] And in Nagaur, India (39%) [62] and 26% in Iran [57]. But higher than study done in IRAN (3.1%) [63].…”
Section: Discussionsupporting
confidence: 90%
“…In our study 27 (11%) Neonates were died due to birth asphyxia after resuscitation which is similar with study done in six sub-Saharan Africa [59] but lower than study done in Tigray 31% [60] and in Jimma 23.2% [61] of Ethiopia and in Tanzania dar es salaam 62.5% [33] And in Nagaur, India (39%) [62] and 26% in Iran [57]. But higher than study done in IRAN (3.1%) [63].…”
Section: Discussionsupporting
confidence: 90%
“…The health worker interview tool was adapted from the quality of care survey tools developed by the Maternal and Child Integrated Program (MCHIP), which were developed and used in several countries, including Ethiopia, Kenya, Madagascar, and Tanzania . The interview tool was modified for the Indonesian context.…”
Section: Methodsmentioning
confidence: 99%
“…,whichweredevelopedandusedinseveralcountries,includ-ingEthiopia,Kenya,Madagascar,andTanzania 16. Theinterviewtool was modified for the Indonesian context.…”
mentioning
confidence: 99%
“…Overall average knowledge score on essential newborn care in India was 78% [10]. In Africa, 79% care providers dried baby with towel, 94% care providers cut cord with clean blade, 43% care providers initiated breastfeeding within the first one hour, 45% care providers placed new born skin to skin contact, and 65% clamped cord when pulsation stop or 2-3 min after birth [11]. Study conducted in Sudan Khartoum showing knowledge of the immediate care of the newborn showed that knowledge level was medium, that is, 50.6% [12].…”
Section: Introductionmentioning
confidence: 99%